Development of a Home-Based COVID-19 Curriculum for Filipino Children - Kaw, Christine Alexandra F (Archīum Ateneo, 2021)
Background: COVID-19 caused educational institutions to transition online, necessitating tailored interventions in spreading factual information. Formal learning in the Philippines has yet to resume physically. Objectives: This methodological and formative research sought to develop a contextualized, home-based, and age-appropriate COVID-19 prevention curriculum for Filipinos within ages 5-8, 9-12, and 13-16. This article describes the process of co-developing the curriculum and identifying key themes in curriculum development which may be relevant to low-middle income countries (LMIC). Methodology: Preliminary curriculum materials were developed based on COVID-19 prevention literature and existing health promotion materials. A focus group discussion (FGD) with eight subject experts was conducted to explore the barriers and facilitators to knowledge and behavioral change. Results were analyzed thematically using predetermined themes: content, structure, delivery, and appropriateness to context. Results: The co-development provided insights through academic, professional, and cultural lenses. Subthemes were generated from content, delivery, structure, and appropriateness to context recommending the use of activities that are engaging and empowering to the child and providing support for carers. Curriculum key outcomes of this research include a clearer, comprehensive, accurate, and contextualized curriculum in relation to the target age groups. Conclusion: Curriculum co-development may be improved by involving key persons in the community. To promote behavioral change and hygienic practices among Filipino children, active, constructive, and interactive learning methods, as well as a motivational approach, must be employed. Major findings for curriculum effectiveness highlighted the importance of the following: prevention-focused materials, accurate and updated information, summary provisions at the curriculum's end, availability of activity materials, household involvement, and open-ended activities. Future research may work on contextualizing other health literacy curricula to the local context and tailoring interventions at the community level.